ANALISIS EFEKTIVITAS SIGNAGE DI FAKULTAS SENI RUPA DAN DESAIN UNIVERSITAS TARUMANAGARA: Analysis of Signage Effectiveness at the Faculty of Fine Arts and Design, Tarumanagara University - Edy Chandra; Matthew Agustino; Budi Darmo (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2025)
Analysis of Signage Effectiveness at the Faculty of Fine Arts and Design, Tarumanagara University. This study analyzes the effectiveness of Signage at the Faculty of Fine Arts and Design (FSRD), Tarumanagara University, in assisting students, faculty members, and visitors in navigating campus facilities. Signage plays a crucial role in visual communication, functioning not only as a directional tool but also as an essential representation of the institution’s identity. Effective signage ensures that users can easily locate classrooms, offices, studios, and other key areas within the campus. This research employs a combination of direct observation methods, Focus Group Discussions (FGD), and literature studies to assess the current state of signage at FSRD. FGD discussions with first-year students highlight frequent difficulties in locating important campus information, emphasizing the need for signage with clearer typography, better contrast, and strategic positioning. Literature studies support these findings, underscoring the significance of a consistent and well-structured wayfinding system. The findings indicate that existing signage remains inadequate in three critical aspects: quantity, design, and informational clarity. Observations reveal that the number of signs available is insufficient, leading to confusion, especially for new students and visitors. Additionally, the placement of signs is often ineffective, reducing their visibility and accessibility. From a design perspective, the visual elements of the signage do not adequately reflect the artistic identity of the faculty, missing an opportunity to reinforce FSRD’s creative and academic branding.